Strategi Public Relations BKKBN dalam Kampanye Nasional Penurunan Prevalensi Stunting Melalui Media Sosial dengan Pendekatan Studi Literature Review - Hakim, Alfi; Amini, Nadia Ushfuri; Siti Nur’aeni; Jabar, Raihan Abdul; Nurridwan, Syuffie Gustin (Jurnal Media Informatika, 2025)
The problem of stunting in Indonesia is a national concern because of its impact on children's physical, cognitive, and health development. This study aims to analyze the Public Relations (PR) strategy implemented by National Population and Family Planning Agency (BKKBN) in the National Campaign to Reduce the Prevalence of Stunting through social media. The research uses a descriptive qualitative approach with a literature study method to examine effective communication strategies in raising awareness, changing behavior, and mobilizing community support. The analysis was carried out using the AIDA (Attention, Interest, Desire, Action) model on Instagram @bkkbnjawabarat social media content. The results of the study show that the PR strategy implemented is able to attract the attention of the audience through interactive visual content, arouse interest with informative messages, foster the audience's desire to be actively involved, and encourage real actions in supporting stunting prevention efforts. The optimization of social media, especially Instagram, allows this campaign to reach a wider audience, especially the younger generation and families. This study concludes that an effective PR approach through social media can accelerate the reduction of stunting prevalence in Indonesia.